2014
DOI: 10.1038/bonekey.2014.83
|View full text |Cite
|
Sign up to set email alerts
|

The hunger games of skeletal metabolism

Abstract: Gastrointestinal peptides and adipokines are critical signalling molecules involved in controlling whole-body energy homeostasis. These circulating hormones regulate a variety of biological responses such as hunger, satiety and glucose uptake. In vivo experiments have established that these hormones also regulate bone metabolism, while associations between these hormones and bone mass have been observed in human clinical studies. With a focus on recent research, this review aims to describe the roles that gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Accordingly, ghrelin levels in the blood of our KOs are significantly higher than in the WTs as tested by ELISA (Figure 4C ). Closing the circle, the literature tells us that ghrelin promotes bone formation either through the induction of growth hormone or through growth hormone-independent mechanisms (Tong et al, 2012 ; Delhanty et al, 2014b ; Wee and Baldock, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, ghrelin levels in the blood of our KOs are significantly higher than in the WTs as tested by ELISA (Figure 4C ). Closing the circle, the literature tells us that ghrelin promotes bone formation either through the induction of growth hormone or through growth hormone-independent mechanisms (Tong et al, 2012 ; Delhanty et al, 2014b ; Wee and Baldock, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Low glycemic levels induce ghrelin secretion in the stomach through sympathetic neurons and the release of norepinephrine (Goldstein et al, 2011 ). Then ghrelin favors bone formation either in a direct way acting on osteoblasts (Ma et al, 2015 ) or through the induction of growth hormone or IGF-1 (Fukushima et al, 2005 ; Deng et al, 2008 ; Tong et al, 2012 ; Delhanty et al, 2014a , b ; Wee and Baldock, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin, a 28-amino acid predominantly produced by the gastric mucosa [ 13 ], has been shown to display appetite-stimulatory effects and induces a positive energy balance leading to body weight gain. Leptin and ghrelin antagonize each other in regulating energy balance [ 14 ]. A number of studies have reported serum leptin and ghrelin level disorders in AIS patients [ 15 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we also measured the serum levels of adiponectin and VEGF. Adiponectin has been identified in osteoblasts and osteoclasts, but the effects of adiponectin on bone mechanism still remain unclear 23 . VEGF is a promoter for osteoblast differentiation and bone mineralization 24 .…”
Section: Resultsmentioning
confidence: 99%